Refusal in Reporting Medication Errors from the Perspective of Nurses in Emergency Ward - Esmaeil MohammadNejad; Seyyedeh Roghayeh Ehsani; Amir Salari; Azam Sajjadi; Ayeshe HajiesmaeelPour (Golestan University of Medical Sciences, 2013)
Background and Objective : Drug administration is considered an important aspect of patient care process and reporting the errors is needed to maintain safety. We aimed to investigate "Perspectives of Nurses about refusing to report the medication errors in Emergency Ward".   Material and Methods : In this descriptive study, 94 Emergency nurses were recruited by census in 2011-2012. The instrument was a researcher-made questionnaire including demographic data and questions related to the causes and factors affecting the reporting of medication errors. Using SPSS-16 software, the data was analyzed by applying descriptive and inferential statistics.   Results: The nurses who did not report medication errors are 72%. The most common type of medication errors are infusion rate(33.3%) and wrong- drug dosage (23.8%). The most important reasons of medication errors are shortage of nursing staff (47.6%) and lack of pharmacological information (30.9%). Most common reasons for refusing to report the medication errors are fear of its negative effect on financial advantages, inappropriate or negative attitude of managers toward reporting errors and lack of importance of reporting from nurses י perspective.   Conclusion: Considering the high rate of refusing to report, it is needed to be created some appropriate conditions to enhance the rate of reporting and removing the barriers. Nursing managers should have positive reaction to nurses' reporting.